Stranger in the Shogun's city : a Japanese woman and her world - Stanley, Amy, 1978- (New York : Scribner, 2020)
"A vivid, deeply researched work of history that explores the life of an unconventional woman during the first half of the 19th century in Edo-the city that would become Tokyo-and a portrait of a great city on the brink of a momentous encounter with the West."--
Faraway Places -- Half a Lifetime in the Countryside -- To Edo -- A View from a Tenement -- Samurai Winter -- Costumes for Urban Life -- Troubles at Home -- In the Office of the City Magistrate -- Endings and Afterlives.
Includes bibliographical references (pages 293-307) and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Tsuneno, -- 1804-1853.; Women -- Japan -- Tokyo -- Social life and customs; Divorced women -- Japan -- Biography; Tokyo (Japan) -- History -- 19th century; Tokyo (Japan) -- Biography; Biographies